Study of dry beneficiation of Kara-Dobo coals and the influence of fractional composition on enric hability (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This study analyzes modern methods of dry coal beneficiation, the influence of fractional composition on process efficiency, optimal technological parameters, and the prospects for dry beneficiation of coals from the Kara-Dobo deposit
Keywords: dry beneficiation, coal, Kara-Dobo, pneumatic beneficiation, fluidized bed, separation, coal fraction, coal density, washability